Desain Robot Pengintai Segala Medan dengan Kendali Wireless PS2 - Mayastri Devana; Tresna Dewi; Nyayu Latifah Husni; Pola Risma; Yurni Oktarina (Journal of Applied Smart Electrical Network and Systems, 2021)
A mobile robots is one of the solution to overcome the deficiency of security surveillance camera systems that are static in nature, which are vulnerable to blind spots on the results of their observations. In this research, the surveillance robot is made to resemble the shape of a mars rover robot that is applied to be able to move more freely to stalk areas and be able to navigate on uneven surfaces. The movement of the surveillance robot wheel uses a wireless PS 2 remote control and is driven by a DC motor rotation as its main drive. The connection between the PS2 Remote Control and the surveillance robot is by using the Arduino Uno. In addition, this robot will be equipped with a camera that will send visual surveillance results from the robot to the smartphone.